(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Bahía Anegada is the coastal zone of the southern part of Buenos Aires Province (Argentina), where several environments are recognized: islands, inlets, marshes, tidal plains and different types of beaches. The Bahía San Blas is located at the southern part of the Bahía Anegada, where the San Blas channel separates the mainland from an island (Fig. 1). The San Blas channel is 2.5 km wide and 12 km long. The study area has a tidal amplitude characterized by a mean of 1.62 m, being 2.20 and 0.58 m the high and low tide respectively. The present study shows the results of a bathymetric survey of the San Blas channel and an analysis of the behavior of the tidal currents that affect sediment transport and promote the generation of different bedforms. The aim of this study was to analyze the submarine geomorphology related to the dynamic conditions in order to characterize in detail the sedimentary conditions in this area. A detailed bathymetric study was conducted over a zone of 50 km2, covering the San Blas channel, through a digital echosounder Bathy-500 positioned by DGPS operating in real time. Fifteen transversal tracks and three longitudinal tracks were made at the San Blas channel in order to obtain the necessary bathymetric profiles to make a bathymetric chart of the area. Over a zone of 1.5 km2, characterized by a field of subaqueous dunes, a Phase Measuring Bathymetric System (FMBS), called swath bathymetry system "GeoSwath Plus" from GeoAcoustics Lt. (UK), was employed in order to determine the detailed dune morphology. This survey yielded details and disposition of the bedforms present on the channel bed with centimetric precision. Bottom sediment samples were collected and tidal currents were measured using an Acoustic Doppler Current Profiler (ADCP) mounted on a ship. The tidal currents were measured during a whole tidal cycle, obtaining the distribution of velocity and direction over the water column, on a track carried out transversally to the channel. These values were computed with the associated WinRiver software. The entire field work (bathymetry, sampling, FMBS and ADCP) was performed with the 6.5 m long boat IADO IV. The coastal features display geomorphological differences in response to a changing dynamic regimen along the channel (Fig. 2). Remarkable morphological and textural differences occur along the coast. Close to the mouth, a dissipative beach, with medium sand and a gentle slope is present. Mobile coastal dunes are common crowning the beach. Nearly the central part, the beach is steeper and composed of gravels developing then a reflective beach. Towards the north, in the inner part of the Bahía Anegada (north of Punta Ramirez), wave-cut platforms and marshes covered with Spartina alterniflora appear, sheltered by cliffs formed by deposits from the Río Negro Formation. The bathymetric map allows distinguishing the existence of significant changes in the morphology throughout the San Blas channel. Based on these differences, the area was divided into 4 zones (Fig. 3), each one with distinctive profiles (Fig. 4). Zones I and II are characterized by a 28 m-depth flat bottom, free of unconsolidated sediments and with steep flanks. These features allow establishing an analogy with a tidal throat. A subaqueous dune field, covering an area of more than 1.5 km2, was found in Zone III. Zone IV is a shallow area where sand bars are exposed during low tide. The dune field was characterized by large dunes, with spacing between 40-80 m and heights of 2.5 m, identified at 21 m depth (Fig. 5). Higher dunes occur in deeper zones, reaching values of 4.5-5 m height at around 24 m depths. Most of the subaqueous dunes located on the southern portion of the dune field exhibit a symmetrical cross section and are covered by smaller bedforms of 0.3-1 m high and 0.7 to 0.9 m of spacing. On the other hand, dunes located on the northern side of the field are asymmetrical, with the steeper side towards the inner part of the channel. The mean grain size in the field dune is between medium and coarse sand (1.8 a 0.28 phi) that is in equilibrium with the strong velocities of tidal currents. The results obtained from the current measurements over a tidal cycle show that maximum velocities measured in the San Blas channel reached 2 m s-1 during flood and 1.8 m s-1 during ebb (Fig. 6). The maximum velocities of the flood currents were attained mainly on the northern flank and central part of the channel almost reaching the bottom. On the other hand, the maximum velocities of the ebb currents were found on the deepest site of the profile, on the southern flank, from mid-water up to the surface. At both ends of the channel, sand accumulates due to the reduction in the carrying capacity which leads to the formation of an ebb and a flood tidal deltas. The sand bars exposed in low tide in the inward shallow part in the Anegada Bay is the tidal flood delta formed by the loss in the sediment transport capacity caused by the widening of the channel section. This unconsolidated granular sediment is available to be transported by the tidal currents. Towards the outer part of the channel, the bathymetric map shows shallower depths while nautical charts confirm the presence of submarine bars at the entrance of the San Blas channel (Fig. 7). These bars might be evidence of the occurrence of an ebb tidal delta. The present study allowed concluding that the San Blas channel is a narrow strait between the mainland and an island, connecting the Anegada Bay with the outer sea and showing different submarine topography. Towards the mouth, the channel presents a flat bottom over 80% of its width, showing a U shape. The bottom is free of unconsolidated sediments due to the strong currents that wash away any loose material. The submarine topography of the San Blas channel corresponds very well with the tidal inlet significance.